2014
DOI: 10.1080/02755947.2014.932868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fish Length and Anatomical Placement on Retention of Visible Implant Alpha Tags in Hatchery‐Reared Rainbow Trout

Abstract: We examined the effects of anatomical placement and fish TL on 8‐month retention of standard‐sized (1.2 × 2.7 mm) visible implant alpha (VIA) tags in 255 Rainbow Trout Oncorhynchus mykiss (128–368 mm TL) at 14‐d intervals in a hatchery setting. Anatomical placement was strongly associated with tag retention at each sampling period following day 154, culminating with significantly fewer (P < 0.05) VIA tags retained in anal fin tissue (25%) than in postorbital adipose tissue (55%) on day 224. Logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Another consideration that researchers must weigh is the visibility of VIA tags, as the majority of VIA tags in this study were unreadable by the end of the experiment. Other studies have found that VIA retention and visibility varies depending upon tag placement (Davis et al 2014), and it is possible that other body locations would have resulted in higher VIA retention rates. Cyprinids lack the adipose eyelid commonly used for VIA placement in salmonids; however, alternate locations, such as the anal fin (Wenburg and George 1995), may prove more suitable.…”
Section: Discussionmentioning
confidence: 97%
“…Another consideration that researchers must weigh is the visibility of VIA tags, as the majority of VIA tags in this study were unreadable by the end of the experiment. Other studies have found that VIA retention and visibility varies depending upon tag placement (Davis et al 2014), and it is possible that other body locations would have resulted in higher VIA retention rates. Cyprinids lack the adipose eyelid commonly used for VIA placement in salmonids; however, alternate locations, such as the anal fin (Wenburg and George 1995), may prove more suitable.…”
Section: Discussionmentioning
confidence: 97%
“…Each fish was anesthetized to stage 4 anesthesia [11] with 60 mg/L Tricaine Methanesulfonate (MS-222; Syndel Ferndale, Washington, USA) and weighed and measured (total length) to the nearest g and mm. Then a unique visual implant tag (VI tag) (1.2 mm, 2.7 mm; Northwest Marine Ecology, Inc., Seattle, Washington, USA) was inserted behind the eye into the postorbital tissue for identification purposes [12]. Handling time to the nearest second was measured from when the fish were removed from the anesthetic water to when fish were placed into the raceway section after surgery.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…retention rates of previous VIA tags have been thoroughly investigated (Hughes et al 2000;Rikardsen et al 2002;Isely et al 2004), long-term and tag location retention rates for current standard VIA tag are largely unknown. Recent evaluations of current standard VIA tags have been short-term (< one year) laboratory studies and researchers reported poor ( 36%) tag retention for salmonids and cyprinids tagged in the cheek, caudal peduncle, ventral jaw, and anal fin (Wagner et al 2013;Davis et al 2014;Neufeld et al 2015). Retention of VIA tags inserted in post-orbital tissue of salmonids (total length [TL] range of 3.3 -> 11.8 in) and Tiger Muskellunge Esox masquinongy X E. lucius (mean TL 3.6 in) ranged from 55% to 100% and in one instance increased with salmonid size (Davis et al 2014;Turek et al 2014).…”
Section: Introductionmentioning
confidence: 99%